Implementasi Library Leaflet Dalam Pemetaan Digital Penyulang Di Unit Layanan Pelanggan Medan Kota - Hafizh, Muhammad Abdurrahman; Samsudin; Triase (Jurnal Teknik Informatika dan Komputer, 2026)
Advances in information technology have facilitated the adoption of digital systems to improve the effectiveness and integration of infrastructure management. In the management of electricity distribution networks, particularly distribution feeders at PT PLN (Persero) ULP Medan Kota, there are still problems related to the presentation of location data that has not been sufficiently digitized. This scenario makes monitoring the position and data of distribution feeders, along with technical decision-making, less than optimal. This study aims to develop a Geographic Information System (GIS) for digital and interactive mapping of distribution feeder locations. This system was created using the Leaflet library for digital mapping, the Laravel framework for application development, and MySQL for managing distribution feeder data information. The system development methodology used is the Waterfall model, which includes the phases of needs analysis, system design, implementation, and testing. Distribution feeder data is presented as an informative digital map, facilitating user understanding of distribution feeder distribution and status. The results of the study indicate that this system can offer distribution feeder information in a digital, structured, and easily accessible manner. Thus, the implementation of this Leaflet-based GIS can improve the effectiveness of management, monitoring, and support decision-making in the management of the electricity distribution network at ULP Medan Kota.